Uso do território e questão habitacional na ilha do Maranhão: a situação geográfica do Conjunto Habitacional Cidade Verde I, Paço do Lumiar – MA - Costa, Cleynice Maria Cunha (2020)
The housing issue, in the urbanization process, is a key issue that demands efforts to break down the various factors and agents linked to its supply and disposition, which have direct implications for the socio-territorial formation of urban spaces. Residencial Cidade Verde I - RCVI, located in the municipality of Paço do Lumiar - MA, is a product of the various agents that contribute to this socio-territorial formation, on Maranhão Island, from the uses of the territory. For the RCVI case, the main agents are the State, based on housing policies, real estate developers, who define the location and impose market logic on the territory, and the social agents, represented by residents of the residential, who fight and conquer your rights and your space. The entire socio-territorial history of Maranhão Island is driven by the dynamics incorporated through housing policies, which materialized in the territory through housing estates. São Luís, as a hub for the urban expansion of Maranhão Island, reached high levels of demographic density and demand for space, especially in the 1980s and 1990s, when this urban expansion joined other municipalities on the island - São José de Ribamar and Paço do Lumiar - manifesting itself in housing estates. Paço do Lumiar, which used to be a rural population until the early 2000s, has as its landmark the urbanization of its territory, the installation of the Maiobão housing complex (1986), having in the 1990s the installation of other housing complexes stemming from Federal Government policies in partnership with the State. Associated with these spaces, spontaneous occupations, a manifestation of socio-territorial inequalities and access to housing, also increased. The territory of Paço do Lumiar became of potential value for real estate speculation. From 2009 with the PMCMV, several housing estates were installed in Paço do Lumiar, including RCVI (2015), forming new mobility and economic flows for the municipality. The housing complexes of the PMCMV are very important in combating the housing deficit, since they cover the social strata of lower purchasing power, and this program is an opportunity to access their own home. However, there are still some problems regarding the location and infrastructure of housing estates, especially tracks 1 and 2. Residents of RCVI, which belongs to track 2 of the Program, face difficulties in accessing goods and services, in mobility and in infrastructure. RCVI houses and roads. There is still a severe disarticulation among the municipalities belonging to the Island, in the resolution of these problems that are metropolitan, since the majority of the population that resides in the PMCMV housing complexes in Paço do Lumiar, lived in São Luís and still maintains their workflows in the capital.